2015
DOI: 10.4236/ajac.2015.611084
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Trace Element Content between Non-Indigenous Farmed and Invasive Bivalve Mollusks of the South African Coast

Abstract: The contents of 23 trace elements (Sc, V, Cr, Mn, Fe, Co, Zn, As, Se, Br, Rb, Sr, Mo, Ag, Sb, I, Ba, La, Ce, Sm, Eu, Hf, Ta) were quantitatively determined in soft tissues and shells of mass non-indigenous bivalve mussels-farmed Pacific oysters (Crassostrea gigas) and farmed and wild invasive Mediterranean mussels (Mytilus galloprovincialis) at the Atlantic coast of South Africa. The study revealed that the contents of the majority of elements in the soft tissues of both species were higher than those in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
(12 reference statements)
1
14
1
1
Order By: Relevance
“…Regarding the remaining elements, Sr and Br contents were similar to the values reported for C. gigas in the South African Atlantic Coast, 45 ± 5 mg/ kg dw and 127 ± 10 mg/kg dw, respectively. In this study, the I content was lower than that of the South African oysters, 10.9 ± 0.4 mg/ kg dw (Pavlov et al, 2015). This is noteworthy, especially for SW100 oysters, which were fed a SW feed rich in I (44.6 ± 0.8 mg/kg dw).…”
Section: Oyster Elemental Compositioncontrasting
confidence: 50%
See 3 more Smart Citations
“…Regarding the remaining elements, Sr and Br contents were similar to the values reported for C. gigas in the South African Atlantic Coast, 45 ± 5 mg/ kg dw and 127 ± 10 mg/kg dw, respectively. In this study, the I content was lower than that of the South African oysters, 10.9 ± 0.4 mg/ kg dw (Pavlov et al, 2015). This is noteworthy, especially for SW100 oysters, which were fed a SW feed rich in I (44.6 ± 0.8 mg/kg dw).…”
Section: Oyster Elemental Compositioncontrasting
confidence: 50%
“…This phenomenon does not seem to result from a lower metabolic rate in the SW0 oysters. A low metabolic rate is sometimes an explanation for low accumulation rates (Pavlov et al, ). Indeed, the viability results associated with this study on broodstock conditioning of C. gigas (Rato et al, ) have shown that SW100 oysters exhibited a higher mortality when compared to SW0 and the remaining feeds, being unable to meet the demands for maintenance—a lower standard metabolic rate was measured in the SW100 oysters than in SW0 oysters (Ozório et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to both the ICP-MS and NAA results, As exhibited the most notable differences. These site-specific differences in the contents of determined elements in the tissues of the mussels can be explained by the differences in the environmental conditions at these sites as suggested by Pavlov et al [13]. The conditions in Danger Bay are more dynamic and challenging for the mussels as they inhabit rocks that are exposed to extreme weather conditions, opposed to the mussels in Saldanha Bay that are always submerged.…”
Section: Resultsmentioning
confidence: 92%